The Effect of Relationship Marketing towards Customers' Loyalty Mediated by Relationship Quality (Case Study in Priority Bank in Niaga) - Endang Ruswanti; Widiyanti Permata Lestari (Universitas Pelita Harapan, 2016)
A large number of banks let people be more free in choosing the best bank for their needs. People can freely switch from one bank to another which makes the loyalty level of bank customers decrease, even though the efforts and cost spent for maintaining the customers is cheaper than the efforts and cost spent on getting new customers. Relationship is one of the answers to the problem, relationship marketing is a marketing principle which emphasizes and takes effort in maintaining good long term relationship with customers. This research aims to, analyze the influence competence, communication, and conflict handling towards relationship quality, mediated by relationship quality, and towards customer loyalty. The research was conducted by collecting quantitative data through questionnaires distributed to 130 respondents. The objects of this research were the priority customers at Niaga Bank, and it used purposive sampling technique. This research conducted by using Structural Equation Model method. The result of this research showed that, (1) relationship marketing which consists of competence component, communication, and conflict handling have significant influence and positively towards relationship quality, partially and simultaneously, (2) relationship marketing have significant influence and positively towards customer loyalty which is mediated by relationship quality, and (3) relationship quality have significant influence and positively towards customer loyalty.